Current trends in the development of accounting and analytical support for tax risk management - Kucherenko , Serhii (FINANCIAL AND CREDIT SYSTEMS: PROSPECTS FOR DEVELOPMENT, 2025)
The object of research within this article is the accounting and analytical support for managing enterprises’ tax risks as an integrated system for collecting, systematizing, interpreting, and analyzing data from financial, managerial, and tax accounting to inform sound decisions in the field of taxation. Its structural foundation consists of three interrelated subsystems—accounting, analytical, and control (audit). The system’s critical characteristics are the timeliness of information and its adaptability to environmental changes. Problem statement. Under conditions of an unstable economy and constant changes in tax legislation, traditional accounting approaches lose effectiveness, complicating the timely identification and minimization of tax risks. Unresolved aspects of the problem. Despite considerable attention to risk management and digital tools, the accounting and analytical support for tax risk management itself remains insufficiently studied; there is a shortage of well-developed solutions for data integration and risk-assessment methodologies. The directions for further research are outlined: improving assessment methods, innovative tax planning, and creating comprehensive models for different industries. Purpose of the article. To define the nature and functions of accounting and analytical support for managing tax risks of business entities, to identify the system’s key components, and to outline the problems, challenges, and trends in the transition from traditional systems to modern digital ones. Presentation of the main material. The methodology relies on analyzing contemporary approaches and practical aspects of implementing adaptive information-analytical systems. Logical generalization, comparison, analysis and synthesis, as well as expert assessments, were applied. The results demonstrated the need to modernize accounting and substantiated the three subsystems as the system’s core; the advisability of integrating separate types of accounting into a single information system has been proven. A conceptual digital model is proposed that combines automated accounting systems, analytical platforms for risk assessment, and electronic audit; positive effects from using digital technologies are recorded, and challenges are outlined—cost, cybersecurity, and regulatory dynamism. The role of SAF-T UA and e-reporting as tools for enhancing transparency and promptness is also emphasized. Conclusions. Accounting and analytical support is a key element of tax risk management; its effectiveness increases under conditions of digitalization, strengthened internal control, staff upskilling, and the use of insurance instruments. Practical steps include the regular calculation of risk indicators, ensuring transparency, applying criteria of voluntary tax compliance, and implementing electronic audit (SAF-T UA).